A case study of a teacher's oral error treatment strategies in an English language classroom - Dlangamandla, F N N (Rhodes University, Faculty of Education, Department of Education, 1996)
Theoretical perspectives on error treatment in second language acquisition research are divided on the effect and desirability of corrective feedback on the learner's output. Theorists like Krashen (1982), believe that correction hampers acquisition because it encourages the learners to avoid difficult structures and to focus on form rather than on meaning, while Long (1977) contends that error treatment possibly speeds up interlanguage development although errors disappear slowly. Edmondson (1985) asserts that bringing errors to the learner's attention helps learning and that error - treatment contributes to consciousness-raising which is important for language acquisition. Research findings present conflicting evidence on the effects of corrective feedback on those for whom correction is meant. Some researchers report no concrete findings on the relationship between corrective feedback and learning outcomes (Hendrickson (1978) and Brock, Day and Long (1986)). Others, for example, Chaudron (1977) and Crookes and Rulon (1985) report differential effects of corrective treatments. Salica, Ramirez and Stromquist and Wren (cited in Chaudron 1988) report some evidence of feedback on error resulting in the learner's ability to self-correct. However, Hendrickson (1978) reports that some direct types of corrective procedures have been found to be ineffective. This research investigated a teacher's oral error treatment policy in different types of English lessons in a situation where L2 pupils study English as a subject according to an LI syllabus. The findings of this case study reveal that the teacher's manner of correction, when he decides to correct, is subtle and indirect. Rarely does he correct overtly and explicitly as his concern is to avoid hurting the error maker's feelings. He defers treatment and ignores most of the oral errors that learners make during classroom interaction. Pupil perceptions of their teacher's corrective treatments were positive although some of the pupils reported that they found his corrections confusing and intimidating at times. Most of them expressed , a wish to have their speech errors attended to explicitly, preferably by their teacher as his treatments were found to be motivational and unabrasive. Some of the pupils were opposed to peer correction for fear of ridicule. They also felt that fellow pupils did not always provide correct treatments. All the pupils in this study were of the opinion that oral error treatment is desirable because they believe that it improves their performance in English.
Keywords: Language and languages -- Study and teaching -- Error analysis; English language -- Study and teaching -- Foreign speakers; English language -- Study and teaching -- Foreign speakers -- South Africa